2020
DOI: 10.3390/en13030632
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of the Heat Balance of an Interactive Glass Wall in A Heating Season

Abstract: The paper presents an evaluation of the energy efficiency of an interactive glass wall (IGW) prototype. It is a design analogous to Trombe wall. It is capable of giving out the solar radiation heat gains after the sunset. It responds interactively to solar exposure and temperature conditions, regulating the thermal resistance adequately to the requirements. The evaluation of the efficiency of the IGW was based on the analysis of density of heat flux measured on the inner surface of the wall. The experiments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The presented research aims at the development of a suitable spectrally selective surface technology that can be used in solar thermal applications in building envelopes (e.g., solar walls for passive heating, as in [36,37]). The paper describes the reasoning behind the development of the low-cost polymer-based foil solar absorber, analysis of its spectral optical parameters, and environmental assessment of its production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presented research aims at the development of a suitable spectrally selective surface technology that can be used in solar thermal applications in building envelopes (e.g., solar walls for passive heating, as in [36,37]). The paper describes the reasoning behind the development of the low-cost polymer-based foil solar absorber, analysis of its spectral optical parameters, and environmental assessment of its production.…”
Section: Discussionmentioning
confidence: 99%
“…Low emissivity barriers [34] and reflective foils [35] have been widely investigated in buildings when opaque building components are designed. However, although existing works (such as [36,37]) suggest that a solar selective absorber is a viable option for the reduction of heating energy consumption, a literature review did not identify an existing solar absorber foil that could be potentially integrated for innovative energy-efficient building-envelope applications.…”
Section: Introductionmentioning
confidence: 99%
“…An interactive glass wall, the structure of which was analogous to the Trombe wall, has been tested under temperate climate conditions. On the basis of the results obtained, it was shown that, as a result of heat flow after sunset, there was a reduction in fluctuations in internal air temperature in the test chamber [19]. The concrete layer in the Trombe wall can also be replaced with PCM-modified ceramic elements.…”
Section: Application Of Pcm In Thermal Storage Wallmentioning
confidence: 99%
“…The first was simulated in TRNSYS with a single air node (ground floor), whereas for the second one two air nodes (ground and first floor) have been used and connected to the same generation system [19]. Both the buildings have the same Window to Wall Ratio (WWR) on each exposure, equal to 13%, 10% and 4% for North/South, East and West [20]. Internal gains (332 W per floor, whose 50% is radiative) [21,22] and natural ventilation (0.5 air-change per hour) were set in accordance to Italian standards.…”
Section: Buildings Descriptionmentioning
confidence: 99%